2021
DOI: 10.1108/ijbm-02-2021-0072
|View full text |Cite
|
Sign up to set email alerts
|

To leave or retain? An interplay between quality digital banking services and customer satisfaction

Abstract: PurposeIn this paper, the authors investigated the impact of quality digital banking services delivered during the COVID-19 pandemic on customers' satisfaction and retention intentions.Design/methodology/approachThis study combined constructs drawn from the E-S-QUAL and BSQ models to measure the impact of digital banking services on subscribers of digital banking services in Ghana. The study utilized structural equation modeling with partial least squares (PLS-SEM) to analyze 395 responses.FindingsResults reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 62 publications
1
27
0
4
Order By: Relevance
“…In this study, Ghana as a case study is used to provide empirical evidence because for the past years, the country was adjudged the fastest growing economy in the world in 2011 (World Bank, 2011). Ghana is recorded to have the second largest economy in the West African sub-region (Bankuoru Egala et al , 2021). Ghana’s growth rate was close to 9% in 2018, among the ten fastest growing economies of Africa in 2019, with a 6.5% growth rate (IMF Report, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, Ghana as a case study is used to provide empirical evidence because for the past years, the country was adjudged the fastest growing economy in the world in 2011 (World Bank, 2011). Ghana is recorded to have the second largest economy in the West African sub-region (Bankuoru Egala et al , 2021). Ghana’s growth rate was close to 9% in 2018, among the ten fastest growing economies of Africa in 2019, with a 6.5% growth rate (IMF Report, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Electronic service quality (e-SQ) is increasingly important in influencing customer evaluations and judgments regarding the quality of e-service delivery in the virtual marketplace. Egala et al [2] defined e-service quality as the extent to which a web site facilitates efficient and effective shopping, purchasing and delivery of product and services. According to Ahmed et al [3] service quality measures have been applied to assess the quality of virtual community web sites and satisfaction with e-commerce channels [4].…”
Section: E Service Qualitymentioning
confidence: 99%
“…In addition, electronic service quality has positively influenced the success of online businesses [1]. This success also often includes the contribution in service of the following factors: electronic service quality of the businesses ; electronic satisfaction of the customers [2], and behavioral intentions of customers [2]. Moreover, Chauhan and Rambabu, 2017 found that economic and cultural factors affect consumer behavior in e-commerce.…”
Section: Introductionmentioning
confidence: 99%
“…While customer satisfaction can help customer retention, market presence and positive corporate image are key to commercial sustainably. In their study, Bankuoru, Boateng & Mensah (2021) have attempted to answer the impact of customer satisfaction customer retention, specifically for Fully Digital Service Banks, which cannot be equated with conventional banks with digital services (Bankuoru Egala, Boateng, & Aboagye Mensah, 2021). In addition, no direct studies highlighted the role of customers' understanding of Islamic finance as the basis for their retention intentions in Islamic banking.…”
Section: Introductionmentioning
confidence: 99%